2017
DOI: 10.1002/nme.5595
|View full text |Cite
|
Sign up to set email alerts
|

The solution of elastostatic and dynamic problems using the boundary element method based on spherical Hankel element framework

Abstract: In this paper, new spherical Hankel shape functions are used to reformulate boundary element method for 2-dimensional elastostatic and elastodynamic problems. To this end, the dual reciprocity boundary element method is reconsidered by using new spherical Hankel shape functions to approximate the state variables (displacements and tractions) of Navier's differential equation. Using enrichment of a class of radial basis functions (RBFs), called spherical Hankel RBFs hereafter, the interpolation functions of a H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…By substituting a and b from relation (13) into Equation (9), it can result to the following relation (for more details, see the works of Hamzehei Javaran and Shojaee 30 and Wang and Liu 34 ):…”
Section: Enrichment Of Spherical Hankel Rbfmentioning
confidence: 99%
“…By substituting a and b from relation (13) into Equation (9), it can result to the following relation (for more details, see the works of Hamzehei Javaran and Shojaee 30 and Wang and Liu 34 ):…”
Section: Enrichment Of Spherical Hankel Rbfmentioning
confidence: 99%
“…According to the literature, shape parameters are constants used in RBFs to increase the accuracy [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. It can be said that any specific problem requires the most suitable shape parameter by its own nature provided that high accuracy is demanded.…”
Section: Buckling Of Rectangular Platementioning
confidence: 99%
“…By way of illustration, conical, multiquadric, inverse multiquadric, Gaussian, and J-Bessel [12] has just one shape parameter, whilst complex Fourier [11] and Hankel RBFs [21][22][23] have two of them. For the Hankel shape functions, n and e are the shape parameters that belong to the set of whole numbers and positive real numbers, respectively.…”
Section: Buckling Of Rectangular Platementioning
confidence: 99%
See 1 more Smart Citation
“…The spherical Hankel radial basis function (RBF) with all of its advantageous features plays the main role here. Recently, the implementations of these functions in solving elastostatic and elastodynamic problems using boundary element method and incompressible viscous flow problems using FEM were presented by Hamzehei Javaran et al There are two kinds of RBFs reported in the literature, including oscillatory and nonoscillatory ones. The conical functions, thin plate splines, Gaussian functions, multiquadric, inverse multiquadric, and compact supported functions can be mentioned as nonoscillatory RBF, while real and complex Fourier RBF and J‐Bessel RBF belong to the oscillatory class.…”
Section: Introductionmentioning
confidence: 99%